Synthesis and characterization of a multiporous SnO2 nanofibers-supported au nanoparticles based amperometric sensor for the nonenzymatic detection of H2O2 - Kader, Md. Ashraful; Nina Suhaity, Azmi; Kafi, A. K. M.; Hossain, Md. Sanower; Mohd Faizulnazrie, Masri; Aizi Nor Mazila, Ramli; Tan, Ching Siang (MDPI, 2023)
The challenges of a heme protein and enzyme-based H2O2 sensor was subdued by developing a highly sensitive and practically functional amperometric gold nanoparticles (Au NPs)/SnO2 nanofibers (SnO2 NFs) composite sensor. The composite was prepared by mixing multiporous SnO2 NFs (diameter: 120–190 nm) with Au NPs (size: 3–5 nm). The synthesized Au NPs/SnO2 NFs composite was subsequently coated on a glassy carbon electrode (GCE) and displayed a well-defined reduction peak during a cyclic voltammetry (CV) analysis. The SnO2 NFs prevented the aggregation of Au NPs through its multiporous structure and enhanced the catalytic response by 1.6-fold. The SnO2 NFs-supported GCE/Au NPs/SnO2 NFs composite sensor demonstrated a very good catalytic activity during the reduction of hydrogen peroxide (H2O2) that displayed rapid amperometric behavior within 6.5 s. This sensor allowed for highly sensitive and selective detection. The sensitivity was 14.157 µA/mM, the linear detection range was from 49.98 µM to 3937.21 µM (R2 = 0.99577), and the lower limit of detection was 6.67 µM. Furthermore, the developed sensor exhibited acceptable reproducibility, repeatability, and stability over 41 days. In addition, the Au NPs/SnO2 NFs composite sensor was tested for its ability to detect H2O2 in tap water, apple juice, Lactobacillus plantarum, Bacillus subtilis, and Escherichia coli. Therefore, this sensor would be useful due to its accuracy and sensitivity in detecting contaminants (H2O2) in commercial products.